Challenges and conditions for reindeer husbandry in Norway, Sweden and Finland - Øystein Holand; Ulrika Hannu; Sirpa Rasmus; Birgitta Åhman (Rangifer)
This report is based on the book "Reindeer Husbandry and Global Environmental Change - pastoralism in Fennoscandia". The book, which was published in 2022, brings together previous and new research compiled within a Nordic collaboration project, ReiGN (Reindeer husbandry in a Globalizing North), funded by NordForsk during the years 2016 – 2021. Grants from NordForsk also funded this report.